2012
DOI: 10.1007/s11605-011-1759-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual Modality Drainage for Symptomatic Walled-Off Pancreatic Necrosis Reduces Length of Hospitalization, Radiological Procedures, and Number of Endoscopies Compared to Standard Percutaneous Drainage

Abstract: DMD for symptomatic WOPN reduces LOH, radiological procedures, and number of ERCPs compared to SPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 39 publications
0
87
1
2
Order By: Relevance
“…[18] It was proved that the use of percutaneous drainage during endoscopic treatment of WOPN decreases the amount of endoscopic and radiological procedures as well as hospitalization time. [17,19] In addition, it increases the efficiency of interventional treatment of WOPN. [17,19] In the described case endoscopic drainage being the only way of access to the necrotic collection was insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] It was proved that the use of percutaneous drainage during endoscopic treatment of WOPN decreases the amount of endoscopic and radiological procedures as well as hospitalization time. [17,19] In addition, it increases the efficiency of interventional treatment of WOPN. [17,19] In the described case endoscopic drainage being the only way of access to the necrotic collection was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…[17,19] In addition, it increases the efficiency of interventional treatment of WOPN. [17,19] In the described case endoscopic drainage being the only way of access to the necrotic collection was insufficient. On the 27th day of endoscopic drainage it became necessary to guide the percutaneous drain under radiological imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to surgical necrosectomy, an endoscopic approach significantly reduces proinflammatory response and improves clinical outcome in ANP patients [52]. However, when used as a single modality approach, it requires more sessions of necrosectomy for definitive treatment than in combination with other interventional procedures [53, 61-63]. A large meta-analysis found that endoscopic necrosectomy has success rate of 81% as a single treatment modality with a complication rate of 36% [64].…”
Section: Management Of Acute Necrotic Collections and Walled-off Necrmentioning
confidence: 99%
“…However, when feasible, DMD may reduce length of hospitalization, radiological procedures and number of endoscopies in these patients. 49 A recent paper had attempted a dual drainage in early pancreatitis by using a trans-papillary (instead of transmural) approach as the second head of drainage in addition to percutaneous drainage. This approach is, therefore, feasible in pancreatic fluid collections which have not yet developed a wall.…”
Section: Modified Step-up Approachmentioning
confidence: 99%